Safety, tolerability, pharmacokinetics, and pharmacodynamic effects of naloxegol at peripheral and central nervous system receptors in healthy male subjects: A single ascending-dose study - Eldon, Michael A.; Kugler, Alan R.; Medve, Robert A.; Bui, Khanh; Butler, Kathleen; Sostek, Mark (Clinical pharmacology in drug development, 2015)
This randomized, double‐blind, placebo‐controlled, ascending‐dose, crossover study evaluated single oral doses of naloxegol (NKTR‐118; 8, 15, 30, 60, 125, 250, 500, and 1000 mg), a PEGylated derivative of naloxone, for safety and tolerability, antagonism of peripheral and central nervous system (CNS) effects of intravenous morphine, and pharmacokinetics. Healthy men were randomized 1:1 to naloxegol or naloxegol‐matching placebo administered with morphine and lactulose in a 2‐period crossover design. Periods were separated by a 5‐ to 7‐day washout. Assessments included safety, tolerability, orocecal transit time (OCTT), pupillary miosis, and pharmacokinetics. The study was completed by 46 subjects. The most common adverse events were somnolence, dizziness, headache, and nausea. Greater reversal of morphine‐induced delay in OCTT occurred with increasing naloxegol dose, demonstrating dose‐ordered antagonism of morphine's peripheral gastrointestinal effects. Forty‐four subjects showed no reversal of pupillary miosis; 2 showed potential partial reversal at 250 and 1000 mg, indicating negligible antagonism of morphine's CNS effects at doses ≤ 125 mg. Rapid absorption, linear pharmacokinetics up to 1000 mg, and low to moderate between‐subject pharmacokinetic variability was observed. The pharmacokinetics of morphine or its glucuronide metabolites were unaltered by concurrent naloxegol administration. Naloxegol was generally safe and well tolerated at single doses up to 1000 mg.